Destination marketing : an integrated marketing communication approach - Pike, Steven (Butterworth-Heinemann, 2015)
"Travellers are spoilt by choice of available holiday destinations. In today's fiercely competitive tourism markets, destination competitiveness demands an effective marketing organisation. Two themes underpin Destination Marketing. The first is the challenges associated with promoting multi-attributed destinations in dynamic and heterogeneous markets and the second is the divide between tourism 'practitioners' and academics. Written by a former 'practitioner', Destination Marketing bridges industry and academia by synthesising a wealth of academic literature of practical value to DMOs."--BOOK JACKET.